Moral Hazard and the Portfolio Management Problem. - Stoughton, Neal M (Journal of Finance, 1993)
This paper investigates the significance of nonlinear contracts on the incentive for portfolio managers to collect information. In addition, the manager must be motivated to disclose this information truthfully. The author analyzes three contracting regimes: (1) first-best where effort is observable, (2) linear with unobservable effort, and (3) the optimal contract within the Bhattacharya-Pfleiderer quadratic class. He finds that the linear contract leads to a serious lack of effort expenditure by the manager. This underinvestment problem can be successfully overcome through the use of quadratic contracts. These contracts are shown to be asymptotically optimal for very risk-tolerant principals.